An Assessment of Person with Disabilities at Vivacity Megamall, Kuching in Sarawak: ENGLISH - Amirulrashid Mus; Mohd Kamaruzaman Musa (Progress in Engineering Application and Technology, 2024)
In Malaysia, the increasing number of persons with disabilities (PWD) has created a demand for the provision of adequate special facilities in public buildings. Evaluation is a process to evaluate the facilities owned by the organization to determine the appropriate specifications based on Malaysian Standard Guidelines (MS) and Unifirm Building By Law (UBBL). In addition to that, the assessment of the facilities provided in the building is also the basis for ensuring that the specifications that need to be followed are met.. There are some facilities provided in public buildings nowadays that are still lacking and unsatisfactory. In addition, there are some facilities that do not follow the MS and UBBL. The purpose of this study is to identify the facilities provided for the disabled and the purpose of the study is to analyze the facilities provided for the PWD according to the MS and the UBBL. This study uses primary and secondary methods with assessment at Vivacity Megamall using a checklist based on the MS. Checklist as a instrument, visual inspection/assessment as a method are used as research instruments. Next, a questionnaire will be used to find out the satisfaction and experience of disabled customers who visit the shopping center. In this study, it is hoped that the management of Vivacity Megamall can provide good cooperation throughout the research. The data obtained is expected to help the management to obtain less data. Based on the data obtained, the management can also identify problems with facilities provided for PWD in addition to helping to ensure the provision of such facilities in a state that satisfies customers. In conclusion, programs or activities involving the association of disabled people need to be held regularly and continuously in shopping centers so that they do not feel marginalized or neglected.